HUBUNGAN TINGKAT PENGETAHUAN IBU TENTANG KELUARGA BERENCANA HORMONAL DENGAN TINGKAT KECEMASAN MENGHADAPI GANGGUAN MENSTRUASI DI KELURAHAN PABLENGAN KABUPATEN KARANGANYAR - Sari, Rossy Yustika; Utami, Yuni Wulan (Jurnal Berita Ilmu Keperawatan, 2009)
Family Program is the arrangement effo2rt of birth for increasing prosperity of mother and his children, but its program is claimed to be able to create and civilizes little family who had happiness on the norm and welfare , so doing program KB is growing the other development programs. To get the goal, its required a knowledge from a mother, where when her usage intrauterine device sometime she met the contraception problem device of a mother. The knowledge obtained from many sources, like education grade, because education had an effect to someone with her knowledge. Knowledge about menstruates disorder for a mother who is using a contraception is expected to anxiety reduced. The objective aim to know the relation between knowledge grade of mother about contraption with anxiety grade when disorder menstruate in Pablengan Karanganyar The research method applied is survey method with Cross Sectional approach.Method of the research is all of population, mother whom early stage applies contraception hormonal who live Pablengan village with total 40 responders. Sample technique taken is total sample method. Hypothesis test is applying Chi Square test where searche for relation of knowledge grade of mother about family plans with anxiety level when meet disorder menstruate. Result of research indicates that majority responders are 31-40 years old, education grade is High School, majority of responder are Housewife, majority of knowledge is good category. There is relation between knowledge grade of mother about homonal KB with anxiety grade when meeting disorder menstruate at Pablengan Karanganyar.